Retroperitoneal intramuscular haemangioma: Imaging features. - Hassan, H. A.; Ab. Hamid, Suzana (Publisher:Hong Kong Academy of Medicine Press., 2010)
Retroperitoneal intramuscular haemangiomas are quite rare. Interruption of the muscle layer by intramuscular cavernous haemangioma raised the suspicion of a soft tissue sarcoma. We discuss the radiological characteristics of a haemangioma compared to soft tissue sarcoma.